EFFECTS OF CASEIN AND ISOCYANATE CONCENTRATIONS AS CROSSLINKERS IN THE FINISHING PROCESS OF GOAT LEATHER FOR SHOE UPPERS - Nais Pinta Adetya; Nur Mutia Rosiati; Sofwan Siddiq Abdullah; Emiliana Anggriyani; Laili Rachmawati; Mustafidah Udkhiyati; Abimanyu Yogadita Restu Aji; Ikmal Khalala (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2026)
This study aimed to investigate the interaction between casein, used as a crosslinker, and binders in the leather coating process and to evaluate the quality of leather produced using casein crosslinkers compared with conventional isocyanate crosslinkers. The research methodology consisted of three stages: preparation and characterization of the crosslinkers, finishing of crust goat leather, and final testing. The FTIR spectrum of casein indicated the presence of stretching vibrations associated with functional groups related to coating performance. Leather quality was evaluated through color fastness to rubbing and leather softness tests. From a chemical reaction perspective, casein shows potential as a crosslinker when used in combination with isocyanate crosslinkers. PUD binders do not directly form covalent bonds with casein through –OH groups under normal conditions; however, strong physical interactions through hydrogen bonding can occur. In the presence of a crosslinker such as isocyanate, covalent reactions may take place, forming a stronger urethane/urea network. The rubbing fastness of all leather samples, except C1 (10 parts casein) and I3 (30 parts isocyanate), met the SNI standard.